Cranio-maxillofacial non-Hodgkin’s lymphoma: Clinical and histological presentation - Scherfler, Sebastian; Freier, Kolja; Seeberger, Robin; Bacon, Claire; Hoffmann, Jürgen; Thiele, Oliver C. (Journal of cranio-maxillofacial surgery, 2012)
Non-Hodgkin’s lymphoma represents about 5% of all malignant lesions of the head and neck. In this study we retrospectively evaluated clinical presentation, histological subtype and long-term prognosis of 42 patients with non-Hodgkin’s lymphoma involving the craniofacial area. The mean age at diagnosis was 64years. More than half of the patients presented with disseminated disease at multiple sites (55%, n=23). In 62% (n=26) the first manifestation was extranodal. The most common affected region was the oral cavity (65%, n=17). Treatment consisted of local therapy, including surgical resection and radiation, as well as chemotherapy with or without local therapy. Recurrence occurred in 31% (n=13) of the treated patients. Mean survival after first diagnosis varied from 17months in patients presenting with diffuse large B-cell lymphoma (DLBCL), to 8.5years in patients with follicular lymphoma. The most common histological subtype is DLBCL. Standard treatment for DLBCL consists of chemotherapy combined with CD 20 monoclonal antibody, even after total resection of the tumour. There is high risk of systemic disease in patients presenting with non-Hodgkin’s lymphoma and high risk of post therapy recurrence.